Kristologi dalam Injil Yohanes - Roy Martin Simanjuntak (JURNAL TERUNA BHAKTI, 2019)
The issue of Christology from time to time is one very interesting theological topics to be discussed, both in intellectual circles, even church leaders in communities grow together in a group of local churches. The spread understanding or information about Christology are numerous and easy to find, therefore believers should to select sources so as not to cause a false understanding that led to the loss of the substance of Christology. It’s inevitable that people who are in this modern era of greatly affect the issue and the development of Christology. This discussion includes the concept Christology from the Bible, and then outlines how where fathers or figures of Christian thinkers to formulate it in a Christian doctrine that Christians are ultimately used in the history of Christianity. Christology that comes from understanding the Bible is acceptable and justified by the believer. In particular, in the Gospel of John is very fullgar when talking about Christology, both His nature as well as the work of God and man and his mission for the salvation of mankind. Abstrak Persoalan Kristologi dari zaman ke zaman merupakan sala satu topik teologi yang sangat menarik untuk dibahas, baik di kalangan intelektual, pemimpin jemaat bahkan juga di komunitas-komunitas kelompok tumbuh bersama dalam sebuah gereja lokal. Pemahaman-pemahaman yang beredar atau informasi tentang Kristologi sangatlah banyak dan mudah untuk menemukannya, oleh karenanya orang percaya mestinya menyeleksi sumber tersebut sehingga tidak menimbulkan pemahaman yang keliru dan berujung pada hilangnya substansi Kristologi tersebut. Tidak bisa dipungkiri bahwa masyarakat yang berada dalam era modern ini sangat mempengaruhi isu dan perkembangan Kristologi. Pembahasan ini meliputi konsep Kristologi yang bersumber dari Alkitab, dan kemudian menguraikan bagaimana bapa-bapa gereja atau tokoh-tokoh pemikir Kristen merumuskannya dalam sebuah doktrin Kristen yang akhirnya dipakai orang Kristen dalam sepanjang sejarah kekristenan. Kristologi yang bersumber dari Alkitab merupakan pemahaman yang dapat diterima dan dibenarkan oleh orang percaya. Secara khusus Injil Yohanes sangat terbuka membahas tentang Kristologi, baik hakikatNya sebagai Allah dan manusia maupun karya dan misiNya untuk keselamatan umat manusia.